Counternarrating Racialized Expectations at School: The Diverse Enactments of "Non-Dominant" Identities Among 1.5-Generation Japanese Immigrant Youth. Issue 4 (3rd July 2016) - Endo, R.
ABSTRACT: This study adds to the research on the education of Asian immigrant adolescents by situating how generation, language, nationality, and race complexly impacted how a group of 1.5-generation Japanese youth have made sense of their multiple "non-dominant" identities as immigrant Americans and transnational students within an urban high school setting that publicly promoted a mission of inclusivity but, in practice, devalued "non-dominant" cultural and linguistic expressions. The findings highlight how the youth have contested the English-only ideologies and racialized expectations at their school through alternative literacies and other diverse enactments of their identities, such as by speaking Japanese or Japanglish (a mix of Japanese and English) and expressing their "Made in Japan" pride through the public display of nationalistic symbols and various bilingual or Japanese-language textual representations. New directions are offered for theorizing 1.5-generation Asian immigrant youth linguistic expressions with implications for practice and theory.